2022
DOI: 10.3389/fimmu.2022.865968
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Novel Neutrophil-Based Biomarkers in the Diagnosis and Prediction of Response to Infliximab Therapy in Crohn’s Disease

Abstract: With the increasing incidence and prevalence, Crohn’s disease (CD) has become one of the most challenging diseases in both diagnosis and treatment of gastroenterology. Evaluation of the disease activity and mucosal healing guides clinical decisions regarding subsequent therapy for CD. In this study, we enrolled a total of 144 patients with CD and 239 healthy controls were enrolled. Clinical characteristics and laboratory parameters of enrolled subjects were retrieved from the electronic medical record database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…NAR has been observed to be significantly increased in patients with IBD, and it has shown positive correlations with both systemic and mucosal inflammation. 9,11 In this study, we underscored the clinical significance of NAR as a biomarker in IBS. Its associations with symptom severity, quality of life (QOL), and inflammatory mediators highlight its potential in guiding treatment strategies and improving patient outcomes.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…NAR has been observed to be significantly increased in patients with IBD, and it has shown positive correlations with both systemic and mucosal inflammation. 9,11 In this study, we underscored the clinical significance of NAR as a biomarker in IBS. Its associations with symptom severity, quality of life (QOL), and inflammatory mediators highlight its potential in guiding treatment strategies and improving patient outcomes.…”
Section: Introductionmentioning
confidence: 78%
“…The neutrophil-to-albumin ratio (NAR) has garnered attention as a valuable marker of systemic inflammation in various medical conditions, including inflammatory diseases, vascular disorders, and cancers. [7][8][9][10][11] Combining blood cell counts and serum biochemical indices, NAR has emerged as an informative parameter in clinical research. Studies have demonstrated the utility of NAR as a diagnostic and prognostic marker in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, timely and effective assessment of drug efficacy is crucial to the prognosis of patients, avoiding delays in treatment and reducing the cost of treatment for patients. Single biomarkers have limitations in predicting disease progression, prompting increased research into combining multiple biomarkers, for example, NAR forecasted the reaction to IFX in Crohn’s disease (CD) patients ( 6 ), neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) were used as new biomarkers of mucosal prognosis for UC patients receiving anti-TNF therapy ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identified a novel serological index, the neutrophil-to-bilirubin ratio (NBR), which was effective in monitoring disease activity and predicting response to infliximab (IFX) treatment in patients with Crohn’s disease (CD). 10 However, the use of NBR in UC has not yet been reported. We thus hypothesized that NBR might be useful in monitoring clinical and endoscopic activity in patients with UC.…”
Section: Introductionmentioning
confidence: 99%